CONODONTS IN XENOLITHS OF SEDIMENTARY ROCKS FROM KIMBERLITE PIPES OF THE DALDYN-ALAKIT AREA (SAKHA) - Tarabukin V.P. (My University, 2003)
Diverse conodont assemblages discovered in xenoliths of sedimentary rocks from kimberlite pipes are analyzed and correlated with zonal stratigraphic scales. Based on the original and published data, a Paleozoic rock sequence that existed in the area at the stage of pipe formation is reconstructed, and its stratigraphic hiatuses serving as criteria for exploration of diamonds are distinguished.
Keywords: Paleozoic; Палеозой